Innervation of the receptors present at the various joints of the pereiopods and third maxilliped of Homarus gammarus (L.) and other macruran decapods (crustacea) - Wales, W.; Dando, M. R.; Laverack, M. S.; Clarac, F. (Zeitschrift fr Vergleichende Physiologie, 1970)
This paper gives a full account of the number and structure of the chordotonal organs present at all joints between the coxopodite and dactylopodite of the pereiopods and 3rd maxilliped of the macruran Homarus gammarus L. ( H. vulgaris M. Ed.). Some comparative data is supplied for other macruran decapods. As the form of the receptors depends to some degree upon the structure of the joint we have included details of musculature, planes of movement and degrees of freedom at each of the joints. Peer Reviewed http://deepblue.lib.umich.edu/bitstream/2027.42/47101/1/359_2004_Article_BF00297736.pdf